Anemia among pregnant women first and second trimester increases risk for low birth weight babies in Wangaya Hospital, Denpasar - I Ketut Labir; I Ketut Tangking Widarsa; Ketut Suwiyoga (Universitas Udayana, 2013)
Low birth weight is one of the major contributors to infant mortality rate (IMR). One of the dominant risk factors for the low birth weight is anemia. This study aimed to investigate the effect of anemia in pregnant women at first and second trimester to the incidence of low birth weight at Wangaya Hospital Denpasar. This study is a retrospective cohort design. The total samples were 150 respondents; 50 pregnant women with anemia in the first trimester, 50 pregnant women with anemia in the second trimester and 50 pregnant women without anemia. Samples were taken from medical records at Wangaya Hospital Denpasar using simple random sampling method. Data were collected by documentation study and data analysis was done using logistic regression. The results showed that pregnant women with anemia in the first trimester were having a risk of 10 times to give low birth weight compared to pregnant women who are not anemia [RR=10.29; 95%CI: 2.21-47.90], whereas pregnant women with anemia in the second trimester were at risk 16 times greater of having a low birth weight baby compared to pregnant women who are not anemia [RR=16; 95%CI: 3.49-73.41]. There was no difference in the incidence of low birth weight among anemia first and second trimester [p=0.297]. We can conluded that anemia among pregnant women in the first and second trimester increased the risk of low birth weight. The results of this study can be used by policy makers to planning prevention strategies to reduce the incidence of low birth weight babies including intensify the antenatal care program for pregnant women.